THE IDEA OF FEMINISM ABOUT CHILDFREE IN THE PERSPEKTIVE ISLAM - Wijayanti, Tri Yuliana (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This research examines Childfree from an Islamic perspective. Childfree is an agreement made by a husband and wife not to have children during their marriage. The idea of ​​chilfree itself is an idea brought by the feminist movement through the idea of ​​gender equality. Through a scientific approach to Islamic thought, researchers try to explore how Islamic views examine the idea of ​​Childfree brought by the feminist movement. By using a descriptive analysis methodology, the researcher found that having offspring in Islam is not something that is required or recommended. However, limiting having children (tahdid an-nasl) is certainly closer to the rukhshah dimension (there are reliefs) for certain conditions such as health factors, not for lifestyle. Therefore, Childfree is clearly prohibited in Islam.